Combination of Music and Guided Imagery on Relaxation Therapy to Relief Pain Scale of Post-Operative Patients - Nur Hidayat; Rudi Kurniawan; Yudisa Diaz Lutfi Sandi; Esti Andarini; Fidya Anisa Firdaus; Heri Ariyanto; Reffi Nantia Khaerunnisa; Henri Setiawan (STIKep PPNI Jawa Barat, 2022)
Aim: This literature review aims to explain the effectiveness of combination relaxation therapies with music and imagery technique to reduce the quality and quantity of pain experienced by post-operative patients. Methods: The research data were identified from 5 journal databases including PubMed, JSTOR, Willey Online Library, Sage Journal and Taylor Francis Online by using the PIOS (Participant, Intervention, Outcomes and Study Design) method and MesH term on advanced search engines. Additional records identified through Google Scholar and Research Gate. The articles that become research data are articles published in 1998–2018 in English version, open access and full-text in the form of original research articles. Results: Eight articles that were screened using PRISMA reviewed without meta-analysis consisted of four articles intervening in a combination of relaxation with music and four articles combining with imagery. Conclusion: The combination of relaxation techniques with music, as well as a combination of relaxation techniques with effective imagery are used to reduce pain. Based on the analysis of the results in several studies, it can be found that patient education about relaxation therapy should be given to all surgical patients to help improve patient’s comfort and enhance tissue healing.